A call to action to reclaim focus on testing and early treatment for HIV, viral hepatitis, sexually transmitted infections and tuberculosis. (September 2022) - Stengaard, Annemarie R; Raben, Dorthe; Leite, Ricardo B; Seyler, Thomas; Lazarus, Jeffrey V; Lambert, Jack; Collins, Ben; Attawell, Kathy; Raahauge, Anne; Rockstroh, Jürgen K; Simões, Daniel; ,
We present the outcomes of the HepHIV 2021 Lisbon & virtual conference held on 5-7 May 2021, including a Call to Action addressing policy and practice implications in the field of earlier and integrated testing for HIV, viral hepatitis, STI and TB and in light of lessons learned from the COVID-19 pandemic. Conference presentations showed that combination prevention and integrated testing and care models for multiple infectious diseases are necessary and feasible in diverse settings. Successful examples of service and system adaptations developed to mitigate impact of the pandemic were shared. Aiming to ensure greater equity in health in current and future health policies and programmes and address the adverse effects of COVID-19, we must learn from the many innovative approaches to service delivery developed in response to the pandemic, many of which have the potential to reach people whose needs were not met by existing models.